2011
DOI: 10.1057/thr.2010.21
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Emotional Intelligence on the Service Performance of Casino Frontline Employees

Abstract: The concept of emotional intelligence (EI) has attracted substantial interest in the popular and organisational psychology literature. Although the predictive validity of EI is likely to depend on the context and focus of interest, researchers have identified a positive relationship between EI and job performance in the case of roles, which involve emotional labour, such as customer service. It offers the prospect of providing insights into job performance that have not been explained by traditional cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 51 publications
4
32
0
1
Order By: Relevance
“…In particular, Kim et al (2012) proposed that employees' service performance involve behaviors that serve and help customers and also employees' positive emotional displays are typically central to the customer service experience, associated with favorable customer evaluations as well. In this way, EI can mitigate the downside of emotional work that is performed by frontline employees and may affect performance during encounters with customers (Prentice & King, 2010). Hence EI can affect employee performance.…”
Section: ⅱ Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Kim et al (2012) proposed that employees' service performance involve behaviors that serve and help customers and also employees' positive emotional displays are typically central to the customer service experience, associated with favorable customer evaluations as well. In this way, EI can mitigate the downside of emotional work that is performed by frontline employees and may affect performance during encounters with customers (Prentice & King, 2010). Hence EI can affect employee performance.…”
Section: ⅱ Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Until now, research on EI has usually focused on the influence of EI on service performance (Prentice & King, 2010;Lee et al, 2013), the relationship between EI and emotional labor (Jung & Yoon, 2014), meta-analysis on EI, job performance, and other individual differences (Joseph & Newman, 2010), as well as organizational effectiveness Park et al, 2012). Previous studies have identified these important constructs and despite its practical and academic expansion, some important questions about EI remain.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Specifically, service organizations offer intangible product to its customer, often involves interactions between service employees and customers during service delivery, and finally, service products are often produced and consumed simultaneously by customers (Bowen & Ford, 2002;Sun et al, 2007). In addition to the service features, service organizations are often challenged with unique and impulsive customers' demands, as well as having to deal with customers from various backgrounds and cultures (Prentice & King, 2011). Bearing in mind the distinct environment of service organizations, Bettencourt et al (2001) suggested that service-oriented OCBs are more appropriate in capturing OCBs of employees working in service organizations.…”
Section: Ocbs and So-ocbsmentioning
confidence: 99%
“…Owing to its robustness in predicting job performance, the need of emotional intelligence (EI) instrument increases worldwide since test adaptation to various cultural contexts and languages is continuously growing. Numerous previous research show the robustness of EI as a predictor to job performance, 1 4 psychological well-being, customer satisfaction, and organization performance. 5 …”
Section: Introductionmentioning
confidence: 97%